Inorganic nanoparticles in organic-inorganic hybrid hosts for planar waveguides - Gonçalves, R. R.; Carturan, G.; Scarpari, S. [UNESP]; Oliveira, D. C. [UNESP]; Bueno, L. A. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Ferrari, M.; Montagna, M.; Rainho, J. P.; Carlos, L. D. (SPIE, the international society for optics and photonics, 2002)
Planar waveguides have been prepared on the ZrO2-(3-glycidiloxypropyl)trimethoxysilane (GPTS) system. Stable sols containing ZrO2 nanoparticles have been prepared and characterized by Photon Correlation Spectroscopy. The nanosized sol was embedded in (3-glycidoxipropyl)trimethoxisilane (GPTS) used as a hybrid host for posterior deposition. The opticalparameters of the waveguides such as refractive index, thickness and propagating modes and attenuation coefficient were measured at 632.8. 543.5 and 1550 nm by the prism coupling technique as a function of the Zr02 content. The planar waveguides present thickness of a few microns and support well confined propagating modes. Er doped samples display weak and broad (δλ≈96nm) emission at 1.5 μm.
Keywords: Erbium; Nanoparticles; Organic-inorganic hybrids; Planar waveguides; Zirconia; Nanostructured materials; Rayleigh scattering; Refractive index; Spectroscopy; Inorganic nanoparticles; Photon correlation spectroscopy; Optical waveguides